2022
DOI: 10.53909/rms.04.02.0158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leadership Styles on Employee Wellbeing and Resilience during COVID-19: A Partial Least Square Approach

Abstract: Purpose:The purpose of this research is to investigate the impact of leadership styles on employee well-being and resilience in private universities in Peshawar during COVID-19. The role of leadership in reducing stress and improving mental and physical health was not investigated in COVID-19, and this area is particularly understudied in the Pakistani context.Methodology:Data has been collected from 203 faculty members of 10 private-sector universities in Peshawar using an adapted questionnaire. The responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…[107] Gom et al [107] indicated that transformational leadership is effective at managing uncertainty, which increases resilience level and the ability to face risk. This is in line with the findings of Muhammad et al [108] who noted that transformational leadership styles can help to improve employee well-being and resilience. Conversely, Mao et al [109] found that authentic leadership can also significantly contribute to the growth of employee resilience.…”
Section: Organizational Factorssupporting
confidence: 92%
“…[107] Gom et al [107] indicated that transformational leadership is effective at managing uncertainty, which increases resilience level and the ability to face risk. This is in line with the findings of Muhammad et al [108] who noted that transformational leadership styles can help to improve employee well-being and resilience. Conversely, Mao et al [109] found that authentic leadership can also significantly contribute to the growth of employee resilience.…”
Section: Organizational Factorssupporting
confidence: 92%
“…Different leadership styles had varying consequences on how employees coped with the unheard-of demanding situations. The findings of the study shed light on these dynamics, emphasizing each high quality and negative effects related to each style (Muhammad et al, 2022).…”
Section: Impact On Employee Performancementioning
confidence: 82%